Pendampingan Pemanfaatan Teknik Brand Voice Melalui Media Digital Sebagai Upaya Peningkatan Strategi Pemasaran UMKM di Kampung Pisugi - Difinubun , Muhamad Fagi (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to increase the income of  UMKM in Pisugi Village, Wamena Regency, using brand voice techniques accessed on electronic devices (cell phones). Brand voice techniques are a way of communicating a brand by displaying an attractive style, logo, language and tone to attract consumers. The presence of brand voice in a product can have a significant effect on sales results both digitally and directly. Marketing techniques like this will increase consumer trust and interest. This training activity uses an inductive approach, mentoring and supervision. The stages of community service implementation begin with a field survey, then conducting analysis and potential owned by the local community. After this training activity, the insight and skills of the UMKM community become more open and trained. So they are able to create loyalty, increase income and consumer trust in the products offered